2019
DOI: 10.1111/pde.14035
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin‐induced sacroiliitis: Case series of four patients and a systematic review of the literature

Abstract: Isotretinoin is the mainstay treatment in severe acne; however, its musculoskeletal adverse effects such as lower‐back pain can be disabling. Herein, we present four cases of isotretinoin‐induced sacroiliitis with variable severity. We also present a review of the literature of isotretinoin‐induced sacroiliitis. All our cases were male and human leukocyte antigen (HLA)‐B27 negative. Sacroiliitis was detected a median of 55 (10‐120) days after isotretinoin initiation. Two patients were responsive to baseline su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
(48 reference statements)
1
10
0
1
Order By: Relevance
“…5,12 But the majority of such case reports declare that HLA-B27 is found negative. 3,6,7,10,[12][13][14] In our case, the patient had a negative HLA-B27 as well. MRI was performed after 3 weeks of her initial pain and it showed increased signal intensity and bone marrow oedema of the sacroiliac joints.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…5,12 But the majority of such case reports declare that HLA-B27 is found negative. 3,6,7,10,[12][13][14] In our case, the patient had a negative HLA-B27 as well. MRI was performed after 3 weeks of her initial pain and it showed increased signal intensity and bone marrow oedema of the sacroiliac joints.…”
Section: Discussionsupporting
confidence: 52%
“…9 In the literature, there are reports of cases of unilateral or bilateral sacroiliitis after isotretinoin use. [3][4][5][6][7][8]10 The mechanism of the sacroiliitis is not understood clearly. It is thought that isotretinoin shows detergentlike effects and induces changes in lysosomal membrane structures, causing degeneration in synovial cells, induces hypersensitivity reactions on these cells, and causes synovial cells to become sensitive to minor or mild traumas.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde 18 farklı olgu bildirimi ve çalışmada toplam 99 izotretinoin ilişkili sakroiliit olgusu bildirilmiştir (5,8,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Bu hastaların özellikleri Tablo 3'te verilmiştir.…”
Section: Discussionunclassified
“…The sacroiliac MRI findings were normal for both patients at the ninth month of modified medical therapy. The authors stated that the severity of ISO-induced sacroiliitis varied from one patient to another [16]. Yilmaz Tasdelen et al reported a 23 year-old male patient with bilateral arthritis of wrist and metacarpophalangeal joints when he was on isotretinoin treatment for cystic acne lesions.…”
Section: Discussionmentioning
confidence: 99%